Melatonin Act as an Antidepressant via Attenuation of Neuroinflammation by Targeting Sirt1/Nrf2/HO-1 Signaling - Ali, Tahir; Hao, Qiang; Ullah, Najeeb; Rahman, Shafiq Ur; Shah, Fawad Ali; He, Kaiwu; Zheng, Chengyou; Li, Weifen; Murtaza, Iram; Li, Yang; Jiang, Yuhua; Tan, Zhen; et al. (Frontiers in Molecular Neuroscience, 2020)
Physical or psychological stress can cause an immunologic imbalance, disturbs the central nervous system followed by neuroinflammation. The association between inflammation and depression has been widely studied in recent years, though the molecular mechanism is still largely unknown. Thus, targeting the signaling pathways that link stress to neuroinflammation might be a useful strategy against depression. The current study investigated the protective effect of melatonin against LPS-induced neuroinflammation and depression. Our results showed that lipopolysaccharide (LPS) treatment significantly induced depressive-like behavior in mice. Moreover, LPS-treatment enhanced oxidative stress, pro-inflammatory cytokines including TNFα, IL-6, and IL-1β, NF-ᴋB phosphorylation and glial cell activation markers including GFAP and Iba-1 in the brain of mice. Melatonin treatment significantly abolished the effect of LPS, as indicated by improved depressive-like behaviors, reduced cytokines level, reduced oxidative stress and normalized LPS-altered Sirt1, Nrf2, and HO-1 expression. However, the melatonin protective effects were reduced after luzindole administration. Collectively, it is concluded that melatonin receptor-dependently protects against LPS-induced depressive-like behaviors via counteracting LPS-induced neuroinflammation.